From Place-Marketing to Place-Making, Examining Boston's Case of Global Transformation. Issue 2 (3rd July 2022) - J. L. Balsas, Carlos
ABSTRACT: Economic globalization intensified at the end of the twentieth century. This paper utilizes the City of Boston, and its late 1990s Millennium Initiative (MI), to examine the role of North American cities in the globalization of society and its economy in particular. The study is anchored in these two research questions: Is Boston's city-region knowledge economy and ensuing culture sufficiently integrated into the overall dynamics of its urban society? How did notions of social and environmental sustainability evolve with increased calls for enhancing World City status? The key finding is that for Boston to become a truly World-Class city, it has to go beyond its short (nonetheless the most extensive in the U.S.) history, landmark buildings, socio-economic, and cultural achievements, ambiance and character, to also sustain and nurture all those who reside, work and visit the city-region appropriately and with solidarity.